BEYOND THE CLASSROOM: EXPERIENTIAL EDUCATION THROUGH THE GLOBAL YOUTH TRENDS FORUM - Yofrina Octika Gultom (Adisam Publisher, 2025)
In a time when young people are most influenced by global issues and are also most effective catalysts for change, education is what will tap their potential. This research explores how Taiwan’s Youth Development Administration’s Global Youth Trends Forum (GYTF) 2024 educates youth and inspires them through global challenge response and intercultural dialogue. With a rapidly changing global landscape where almost one in four young people are in NEET (Not in Education, Employment, or Training), youth empowerment is critical to building resilient and inclusive societies. The Global Youth Trends Forum (GYTF) 2024, “Connect and Engage: Global Partnership for Youth,” brought young leaders from Taiwan and worldwide to exchange in interactive sessions around Sustainable Development Goals (SDGs), leadership, and global citizenship. Adopting a qualitative methodology, this study conducted participant observation, taking notes in the field, reflexive journaling, and informal interviews to obtain detailed information about young people’s experience and interaction during the forum. Using the Positive Youth Development (PYD) framework, the study conceptualizes youth empowerment as a development of core values like competence, confidence, connection, character, and caring that equips young individuals with the capacity for becoming global transformative leaders. Thematic analysis yielded important findings: increased SDG awareness (particularly of Goals 4, 10, and 17), productive intercultural collaboration, and heightened confidence and motivation in participants. Youth learned not only through expert panels but also through discussion with peers at a deep and participatory level. Although there was decent participation from external sources, there were very few activities in this study that facilitated personal reflection and personal development. Applying the Inner Development Goals (IDGs) framework such as mindfulness, emotional intelligence, and resilience is recommended in future forums to empower youth to be more engaged and have a long-term influence. This paper argues that youth forums such as GYTF can be great platforms for global education and youth empowerment. If well designed to build both external knowledge and inner development, they prepare young people to address global challenges but also build inner capacities to be capable of ethical and transformative leadership.